Cervical diverticulitis: a novel complication of a neonatal colonic interposition graft following oesophagectomy. (9th September 2015) - Punwani, Vishal V; Ong, Eugene; Hii, Michael W
Abstract : A 47-year-old woman presented to a tertiary emergency department with an 8-day history of odynophagia, a 4 cm swelling on her left neck and intermittent fevers. Shortly following her birth, a congenital oesophageal atresia had been managed surgically with colonic interposition graft. Contrast CT of the neck demonstrated several large diverticula within her interposition graft at the level of the cervical vertebrae. A colocutaneous fistula was identified between the colon and left neck, with an associated abscess. The patient received intravenous meropenem followed by abscess drainage. A high output fistula developed at the drainage site, and the patient required intravenous fluids and stoma placement to manage fluid discharge. She left the hospital after a 17-day stay. At 6-month follow-up, the wound was erythematous, but the patient was otherwise well. We believe that this is the first reported case of diverticular disease arising in what was originally neonatal colon interposed for oesophageal atresia at birth.